Meeting report: 11th international symposium on testate amoebae (ISTA-11 Niagara), Brock University, Canada, June 22–27, 2025 - Francine M.G. McCarthy; R. Timothy Patterson; Florin Pendea (Protist, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Organic matter is a predominant control on total mercury concentration of near-surface lake sediments across a boreal to low Arctic tundra transect in northern Canada - Jennifer M. Galloway; Michael B. Parsons; Omid H. Ardakani; Hendrik Falck; Richard E. Fewster; Graeme T. Swindles; Hamed Sanei; Michael J. Palmer; Nawaf A. Nasser; R. Timothy Patterson (Science of The Total Environment, 2024)

Quantifying conditions required for varve formation in meromictic Crawford Lake, Ontario, Canada: important process for delimiting the Anthropocene epoch - Brendan M. Llew-Williams; Francine M. G. McCarthy; Andrea M. Krueger; Nicholas L. Riddick; Michael D. MacKinnon; Krysten M. Lafond; R. Timothy Patterson; Nawaf A. Nasser; Martin J. Head; Michael F. J. Pisaric; Kevin W. Turner; Joseph I. Boyce; et al. (Journal of Paleolimnology, 2024)

Perceptions of Freshwater Algal Blooms, Causes and Health among New Brunswick Lakefront Property Owners - Sapriya Birk; J. David Miller; Aidan MacMullin; R. Timothy Patterson; Paul J. Villeneuve (Environmental Management, 2023)

Impact of Post-Tropical Storm Arthur (2014) on benthic Arcellinida assemblage dynamics in Harvey Lake, New Brunswick, Canada - Dan Atasiei; Nawaf A. Nasser; Calder W. Patterson; Anqi Wen; R. Timothy Patterson; Jennifer M. Galloway; Helen M. Roe (Hydrobiologia, 2022)

A portable extruder for accurate and precise high-resolution subsampling of unconsolidated sediment cores - R. Timothy Patterson; Nawaf A. Nasser; Steven Tremblay; Jennifer M. Galloway (Journal of Paleolimnology, 2022)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

Ecosystem state shifts during long‐term development of an Amazonian peatland - Graeme T. Swindles; Paul J. Morris; Bronwen Whitney; Jennifer M. Galloway; Mariusz Gałka; Angela Gallego‐Sala; Andrew L. Macumber; Donal Mullan; Mark W. Smith; Matthew J. Amesbury; Thomas P. Roland; Hamed Sanei; et al. (Global Change Biology, 2018)
The most carbon (C)‐dense ecosystems of Amazonia are areas characterized by the presence of peatlands. However, Amazonian peatland ecosystems are poorly understood and are threatened by human activities. Here, we present an investigation into long‐term ecohydrological controls on C accumulation in an Amazonian peat dome. This site is the oldest peatland yet discovered in Amazonia (peat initiation ca. 8.9 ka BP ), and developed in three stages: (i) peat initiated in an abandoned river channel with open water and aquatic plants; (ii) inundated forest swamp; and (iii) raised peat dome (since ca. 3.9 ka BP ). Local burning occurred at least three times in the past 4,500 years. Two phases of particularly rapid C accumulation (ca. 6.6–6.1 and ca. 4.9–3.9 ka BP ), potentially resulting from increased net primary productivity, were seemingly driven by drier conditions associated with widespread drought events. The association of drought phases with major ecosystem state shifts (open water wetland–forest swamp–peat dome) suggests a potential climatic control on the developmental trajectory of this tropical peatland. A third drought phase centred on ca. 1.8–1.1 ka BP led to markedly reduced C accumulation and potentially a hiatus during the peat dome stage. Our results suggest that future droughts may lead to phases of rapid C accumulation in some inundated tropical peat swamps, although this can lead ultimately to a shift to ombrotrophy and a subsequent return to slower C accumulation. Conversely, in ombrotrophic peat domes, droughts may lead to reduced C accumulation or even net loss of peat. Increased surface wetness at our site in recent decades may reflect a shift towards a wetter climate in western Amazonia. Amazonian peatlands represent important carbon stores and habitats, and are important archives of past climatic and ecological information. They should form key foci for conservation efforts.

Hydrology of the North Klondike River: carbon export, water balance and inter-annual climate influences within a sub-alpine permafrost catchment - Anthony Lapp; Ian D. Clark; Andrew L. Macumber; R. Timothy Patterson (Isotopes in Environmental and Health Studies, 2017)

Sequential sample reservoirs for Itrax-XRF analysis of discrete samples - Braden R. B. Gregory; Eduard G. Reinhardt; Andrew L. Macumber; Nawaf A. Nasser; R. Timothy Patterson; Shawn E. Kovacs; Jennifer M. Galloway (Journal of Paleolimnology, 2017)

Taxonomy of the order Mononegavirales: update 2016 - Claudio L. Afonso; Gaya K. Amarasinghe; Krisztián Bányai; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Nicolás Bejerman; Kim R. Blasdell; François-Xavier Briand; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; et al. (Archives of Virology, 2016)

Erratum to: Influence of ocean–atmospheric oscillations on lake ice phenology in eastern North America - R. Timothy Patterson; Graeme T. Swindles (Climate Dynamics, 2015)

Influence of ocean–atmospheric oscillations on lake ice phenology in eastern North America - R. Timothy Patterson; Graeme T. Swindles (Climate Dynamics, 2015)

Middle to late Holocene chironomid-inferred July temperatures for the central Northwest Territories, Canada - Lindsay M. Upiter; Jesse C. Vermaire; R. Timothy Patterson; Carley A. Crann; Jennifer M. Galloway; Andrew L. Macumber; Lisa A. Neville; Graeme T. Swindles; Hendrik Falck; Helen M. Roe; Michael F. J. Pisaric (Journal of Paleolimnology, 2014)

Process length variation of the cyst of the dinoflagellate Protoceratium reticulatum in the North Pacific and Baltic‐Skagerrak region: calibration as an annual density proxy and first evidence of pseudo‐cryptic speciation - Kenneth Neil Mertens; Manuel Bringué; Nicolas Van Nieuwenhove; Yoshihito Takano; Vera Pospelova; Andre Rochon; Anne De Vernal; Taoufik Radi; Barrie Dale; R. Timothy Patterson; Kaarina Weckström; Elinor Andrén; et al. (Journal of Quaternary Science, 2012)
Process length variation of cysts of the dinoflagellate Protoceratium reticulatum (Claparède et Lachmann) Bütschli in surface sediments from the North Pacific was investigated. The average process length showed a significant inverse relation to annual seawater density: σ t annual = −0.8674 × average process length + 1029.3 ( R 2 = 0.84), with a standard error of 0.78 kg m −3 . A sediment trap study from Effingham Inlet in British Columbia revealed the same relationship between average process length and local seawater density variations. In the Baltic–Skagerrak region, the average process length variation was related significantly to annual seawater density: σ t annual = 3.5457 × average process length − 993.28 ( R 2 = 0.86), with a standard error of 3.09 kg m −3 . These calibrations cannot be reconciled, which accentuates the regional character of the calibrations. This can be related to variations in molecular data (small subunit, long subunit and internal transcribed spacer sequences), which show the presence of several genotypes and the occurrence of pseudo‐cryptic speciation within this species. Copyright © 2012 John Wiley & Sons, Ltd.

A sledge microtome for high resolution subsampling of freeze cores - Andrew L. Macumber; R. Timothy Patterson; Lisa A. Neville; Hendrik Falck (Journal of Paleolimnology, 2011)

Controls on the contemporary distribution of lake thecamoebians (testate amoebae) within the Greater Toronto Area and their potential as water quality indicators - Helen M. Roe; R. Timothy Patterson; Graeme T. Swindles (Journal of Paleolimnology, 2010)

Postglacial vegetation and climate dynamics in the Seymour‐Belize Inlet Complex, central coastal British Columbia, Canada: palynological evidence from Tiny Lake - Jennifer M. Galloway; Christine T. Doherty; R. Timothy Patterson; Helen M. Roe (Journal of Quaternary Science, 2009)
A pollen‐based study from Tiny Lake in the Seymour‐Belize Inlet Complex of central coastal British Columbia, Canada, permits an evaluation of the dynamic response of coastal temperate rainforests to postglacial climate change. Open Pinus parklands grew at the site during the early Lateglacial when the climate was cool and dry, but more humid conditions in the later phases of the Lateglacial permitted mesophytic conifers to colonise the region. Early Holocene conditions were warmer than present and a successional mosaic of Tsuga heterophylla and Alnus occurred at Tiny Lake. Climate cooling and moistening at 8740 ± 70 14 C a BP initiated the development of closed, late successional T. heterophylla –Cupressaceae forests, which achieved modern character after 6860 ± 50 14 C a BP, when a temperate and very wet climate became established. The onset of early Holocene climate cooling and moistening at Tiny Lake may have preceded change at more southern locations, including within the Seymour‐Belize Inlet Complex, on a meso‐ to synoptic scale. This would suggest that an early Holocene intensification of the Aleutian Low pressure system was an important influence on forest dynamics in the Seymour‐Belize Inlet Complex and that the study region was located near the southern extent of immediate influence of this semi‐permanent air mass. Copyright © 2008 John Wiley & Sons, Ltd.

Diatoms and pollen as indicators of water quality and land-use change: a case study from the Oak Ridges Moraine, Southern Ontario, Canada - Melissa A. Watchorn; Paul B. Hamilton; Thane W. Anderson; Helen M. Roe; R. Timothy Patterson (Journal of Paleolimnology, 2008)

Multi-proxy evidence of postglacial climate and environmental change at Two Frog Lake, central mainland coast of British Columbia, Canada - Jennifer M. Galloway; R. Timothy Patterson; Christine T. Doherty; Helen M. Roe (Journal of Paleolimnology, 2007)

A paleolimnological record of Holocene climate and environmental change in the Temagami region, northeastern Ontario - Robert E. A. Boudreau; Jennifer M. Galloway; R. Timothy Patterson; Arun Kumar; Frederick A. Michel (Journal of Paleolimnology, 2005)

Arcellaceans (thecamoebians) as indicators of land-use change: settlement history of the Swan Lake area, Ontario as a case study - R. Timothy Patterson; Andrew Dalby; Arun Kumar; Lori A. Henderson; Robert E.A. Boudreau (Journal of Paleolimnology, 2002)

Evidence for rapid avian-mediated foraminiferal colonization of Lake Winnipegosis, Manitoba, during the Holocene Hypsithermal - R. Timothy Patterson; W. Brian McKillop; Sid Kroker; Erik Nielsen; Eduard G. Reinhardt (Journal of Paleolimnology, 1997)